Titanium dioxide modified with transition metals and rare earth elements: Phase composition, optical properties, and photocatalytic activity - Tobaldi, D. M.
A series of titania-transition metal and titania rare earth element mixtures, with the stoichiometry Ti1-xMxO2, where M=Ce, Eu, La, Nb, W, Y, and x ranging from 0 to 0.05 atoms per formula unit, were prepared via solid-state reaction of the precursor oxides. The products of the synthesis were thermally treated in air and two maximum temperatures (900 and 1000 degrees C) were reached. The addition of transition metal and rare earth ions to the TiO2 structure modified the anatase-to-rutile phase transition temperature, depending on the valence state of the ions added. Transition metals entered the titania structure, but essentially no solid solution between the rare earth elements and TiO2 was detected. The photocatalytic activity of the powders was assessed in liquid-solid and gas-solid phases, under UVA and visible-light irradiation, monitoring the degradation of an organic dye and isopropanol, respectively. The results were explained by taking into account the relative amounts of anatase and rutile in the samples, the specific surface area of the powders, and their optical properties. (C) 2012 Elsevier Ltd and Techna Group S.r.l. All rights reserved.